2014
DOI: 10.3386/w20006
|View full text |Cite
|
Sign up to set email alerts
|

Does Classroom Time Matter? A Randomized Field Experiment of Hybrid and Traditional Lecture Formats in Economics

Abstract: The authors thank participants at the Ausschuss für Bevölkerungökomik 2014 conference in Linz and seminar participants at the CUNY Graduate Center and Queens College for helpful comments. Jaeger and Joyce acknowledge support from a CUNY Collaborative Incentive Research Grant (CIRG), Round 20. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 16 publications
3
30
2
Order By: Relevance
“…We found that students in the hybrid sections relied heavily on the time they did have with professors, and that those in side-by-side tests reported lower levels of satisfaction and felt that they learned less. This finding is consistent with other large-scale studies (Bowen et al, 2014;Figlio et al, 2013;Joyce, Crockett, Jaeger, Altindag & O'Connell, 2014) and may suggest a higher perceived value of classroom time. The variation of student responses across our set of test cases suggests that student reactions to hybrid formats may depend on the nature of the course, the quality of the online materials, and how effectively they are integrated into the course.…”
Section: Resultssupporting
confidence: 92%
“…We found that students in the hybrid sections relied heavily on the time they did have with professors, and that those in side-by-side tests reported lower levels of satisfaction and felt that they learned less. This finding is consistent with other large-scale studies (Bowen et al, 2014;Figlio et al, 2013;Joyce, Crockett, Jaeger, Altindag & O'Connell, 2014) and may suggest a higher perceived value of classroom time. The variation of student responses across our set of test cases suggests that student reactions to hybrid formats may depend on the nature of the course, the quality of the online materials, and how effectively they are integrated into the course.…”
Section: Resultssupporting
confidence: 92%
“…An initial randomized trial of a college statistics course found no difference in student achievement in online versus in-person course sections (Bowen et al 2014), but two recent studies have found negative impacts of switching from in-person to online instruction on course final grades in an introductory economics class (Alpert, Couch and Harmon 2014;Joyce et al 2014). Additionally, we recently conducted a resume audit experiment and found that employers are less likely to contact otherwise-identical fictitious job applicants when they have business degrees from online for-profit institutions as compared to degrees from non-selective public institutions (Deming et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have mentioned the lack of personalization as one of the major challenges in eLearning. Joyce et al (2014) demonstrate that while high-achievers perform equally regardless of the format, low-achievers perform worse in the hybrid format. Moreover, the performance of the students is negatively affected if the hybrid classes are based in large lecture halls.…”
Section: Current Research In Elearningmentioning
confidence: 94%
“…The same study summarizes that eLearning is only marginally better than face-to-face learning. However, Joyce et al (2014) compare hybrid classes with face-to-face classes and find that students in the traditional learning format perform significantly better than the students in the hybrid format. The performance outcome measures for learning in these studies include individual exam scores, assignment and quiz performance, and overall course grades (Lack, 2013).…”
Section: Current Research In Elearningmentioning
confidence: 95%